Ramayana Department Store Post-Pandemic: Sharia-Based Recovery and Growth Strategies - Trinanda Aprilia; Abdur Rohman (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2026)
The COVID-19 pandemic has impact on the retail sector in Indonesia, including Ramayana, one of the country's leading retailers. This article discusses the strategic steps taken by Ramayana to recover and thrive after the pandemic, especially in the face of significant market changes. Significant market changes. The main focus of this strategy includes digital transformation, improved customer experience, product innovation, and adjustment to changing consumer habits. Adjustments to changing consumer habits. Digital transformation was carried out by developing an online shopping platform to meet the needs of customers' needs for an online shopping experience. On the other hand, efforts to improve customer service is a priority to create an both in physical stores and online. Ramayana also innovates by products that are in line with the latest market trends, while at the same time branding strategy to maintain the loyalty of existing customers and attract new ones.new customers. Regular evaluations and adjustments to strategies have helped Ramayana remain relevant in the midst of economic challenges and the changes in consumer spending patterns. This study provides valuable guidance for other retailers, emphasizing the importance of innovation, adaptation and a consumer-focused approach to achieving growth. consumer-focused approach to achieving sustainable growth. sustainable growth.